Stability for a system of two coupled nonlinear oscillators with partial lack of damping. (February 2019) - Moroşanu, Gheorghe; Vladimirescu, Cristian
Abstract: The stability of the null solution of a system of differential equations describing two coupled nonlinear oscillators, one being with lack of damping, is discussed. Under certain assumptions we derive some stability results (see Theorems 3.1 and 4.1), which are in agreement with physical reality.